MITIGASI KEGAGALAN INSULATION UDARA DI ZONA RIGHT OF WAY (ROW) PADA KETINGGIAN POHON PARASERIANTHES-FALCATARIA - Utama, Budi; Yuliani, Oni; Handayani, Trie (Institut Teknologi Nasional Yogyakarta, 2020)
Abstract Total blackouts (on August 04, 2019) in the Special Capital Region of Jakarta have an impact to daily the economy and the cessation of MRT (Mass Rapid Transit) public transportation services, as well as public communication systems. The determination of the value of the voltage gradient for knowing of the black-out was used the method of analyses to the exposure of the electric fields under the Extra High Voltage (EHV) transmission lines 500 kV, at the span of the tower T.434 and T.435 in Malon hamlet, Gunung-Pati village, districts of Gunung-Pati, Semarang city - central Java. The analysis of the electric field exposured has been carried out in a simulation using a Matlab softwere by solving the simultaneous equations model that corresponding to the tower configuration system and how many conductors were used. The results of the simulation showed that there was a failure of air insulation between phase conductors and the trees of Sengon (Paraserianthes-Falcataria) at a value of voltage gradient of 32 448.10 kV / m, 66 861.13 kV / m, and 33 129.75 kV / m, each were for the lateral distance of 10 m, 12 m, and 14 m from the tower axis T.434 and T.435. Keywords: Mitigation, ROW, Paraserianthes-Falcataria, Transmission-lines